Histopathological Effects of Gammalin 20 on African Catfish (Clarias gariepinus) - Lawrence Ezemonye; Temiotan Emmanuel Ogbomida (Applied and Environmental Soil Science)
Clarias gariepinus fingerlings exposed to lethal and sublethal concentrations of Gammalin 20 were investigated in a renewal static bioassay with particular reference to behaviour, survival, and histopathological changes. Early symptoms of gammalin 20 lethal poisoning were, respiratory distress, increased physical activity, convulsions, erratic swimming, loss of equilibrium, and increased breathing activity. Behavioural response was dose dependent and decreased with decreased concentration. The 96-hour lethal concentration (LC50) value was 30 ppb. Histopathological changes of the gill, liver, and intestinal tissues of fish treated with sublethal concentration of gammalin 20 for twelve weeks showed gill distortion and fusion of adjacent secondary lamella as a result of hyperplasia and excessive mucus accumulation. The liver showed swelling of hepatocytes with mild necrosis, pyknosis, and vacuolation, while the intestine showed yellow bodies of the lamina propria at the tip of the mucosal fold.